Preparation method of hollow fiber nanofiltration composite membrane with stable flexible structure
By modifying the base membrane surface of the hollow fiber nanofiltration membrane using PEBAX and forming an ether-bonded polyamide separation layer, the problem of insufficient binding force between the separation layer and the base membrane is solved, and the stability and filtration performance of the membrane are significantly improved.
Patent Information
- Application Number
- CN202411815812.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-11
AI Technical Summary
After the hollow fiber nanofiltration membrane is running for a long time, the separation layer and the base membrane are prone to separation, and the binding force is insufficient, resulting in the separation layer being easily shedded.
The base film surface modification is performed using PEBAX, a polymer material with both ether bonds and amide bonds, and reacts with polyamide chloride through interfacial polymerization to form an ether bond-rich polyamide separation layer to enhance the binding force between the base film and the separation layer.
It significantly improves the structural stability of the hollow fiber nanofiltration membrane, can operate for a long time in a hydraulic environment with high pressure and high flow velocity, and improves the desalination rate and water flux.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a method for preparing a hollow fiber composite membrane. Background Art
[0002] The current mainstream commercial nanofiltration membrane products are in the form of flat membranes, which are rolled together with grids to form roll-type elements for use. The water channel structure filled with grids will cause large pressure loss in the elements and reduce the recovery efficiency of hydraulic flushing and chemical cleaning. In the actual nanofiltration process, the roll-type elements have poor pollution resistance when treating complex water bodies. Existing studies have shown that the accumulation of pollutants in the grid area is more serious than the pollution on the membrane surface. In order to alleviate the impact of membrane pollution, it is usually necessary to strengthen the pretreatment process at the front end of the membrane process to reduce the pollutant components of the nanofiltration influent, but this will increase the operating cost of the entire treatment.
[0003] Hollow fiber nanofiltration membrane is a nanofiltration membrane material based on hollow fiber with nanofiltration separation characteristics. Compared with traditional flat rolled nanofiltration membrane elements, it has the characteristics of high flux, low pressure, and pollution resistance. The self-supporting structure of hollow fiber can save unnecessary auxiliary components, so it has a greater filling density. Therefore, the water flux per unit volume of this configuration element can usually be more than doubled compared with the rolled element. In addition, the internal water inlet flow channel of the hollow fiber membrane element is highly open, and pollutants are more easily discharged with concentrated water. It has better pollution resistance and cleaning efficiency, so its pretreatment and subsequent maintenance are simpler. The characteristics of high flux, low pressure, and pollution resistance make hollow fiber nanofiltration membrane have obvious advantages in the field of large-scale municipal water supply deep treatment.
[0004] Although the separation membrane in the form of hollow fiber has the above advantages, the separation layer and the hollow fiber base membrane are prone to separation after long-term operation. This is because the interface curvature between the base membrane and the separation layer is large and the stress is not released. The traditional interfacial polymerization membrane preparation method anchors the separation layer to the surface of the base membrane through weak physical action. The bonding force between the two is insufficient, resulting in the separation layer easily falling off from the base membrane. Summary of the invention
[0005] In order to overcome the problems existing in hollow fiber nanofiltration membranes, the present application provides a polyamide film material with a stable and flexible structure and a preparation method thereof.
[0006] The technical solution adopted to achieve the purpose of the present invention is:
[0007] (1) A hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 40,000-80,000 Da) is used as a base membrane, and the hollow fiber ultrafiltration membrane is immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use. The material of the ultrafiltration membrane can be one of polysulfone, polyethersulfone, polyethylene, polypropylene, and polyvinylidene fluoride;
[0008] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in an alcohol solution containing 0.1-0.5% (mass concentration) of polyether block polyamide (PEBAX) for 1-5 minutes, wherein the molecular weight of PEBAX can be selected from 8000, 10000, and 30000Da, and the alcohol solvent can be selected from isopropanol, n-pentanol, and n-hexanol;
[0009] (3) taking the base film out of the alcohol solution, hanging it vertically in the air for 1-10 minutes, wiping off the excess solution with a paper towel, and then placing it in a hot drying oven at 30-60° C. for 5-10 minutes;
[0010] (4) re-immersing the outer surface of the base film in a 1-4% (mass concentration) aqueous solution of polyetheramine (PEA) for 1-5 minutes, wherein the molecular weight of PEA can be selected from 200, 400, and 2000 Da; then taking it out and hanging it vertically in the air for 1-10 minutes, and wiping off the excess solution with a paper towel;
[0011] (5) immersing the base film again in a 0.1-1% (mass concentration) organic phase solution of a polyacyl chloride monomer for 1-10 minutes, wherein the polyacyl chloride monomer may be one of succinyl chloride, diphenyl diacetyl chloride, 4,4'-oxybis(benzoyl chloride), trimesoyl chloride or a mixture thereof, and the organic solvent may be one of pentane, hexane, cyclohexane, heptane or a mixture thereof;
[0012] (6) The base membrane is taken out from the organic phase, placed in a forced air drying oven at 60-120° C. for 10-30 minutes, and washed with water to obtain a polyamide hollow fiber nanofiltration composite membrane.
[0013] Preferably, in the above step (1), the molecular weight cut-off of the hollow fiber ultrafiltration base membrane is 50,000-60,000 Da;
[0014] Preferably, the mass concentration of PEBAX in the above step (2) is 0.2-0.4%.
[0015] Preferably, in the above step (2), the immersion time of the base film in the alcohol solution is 2-4 minutes.
[0016] Preferably, the molecular weight of PEBAX in the above step (2) is 10000Da;
[0017] Preferably, the heat treatment temperature in the above step (3) is 40-50° C., and the heat treatment time is 6-8 minutes;
[0018] Preferably, in the above step (4), the mass concentration of PEA is 2%-3% and the molecular weight is 400Da;
[0019] Preferably, in the above step (4), the immersion time of the membrane in the water phase is 2-4 minutes;
[0020] Preferably, the concentration of the polyacyl chloride monomer in the above step (5) is 0.2%-0.5%;
[0021] Preferably, in the above step (5), the immersion time of the basement membrane in the organic phase is 2-5 minutes;
[0022] Preferably, in the above step (6), the oven temperature is 80-100° C. and the heat treatment time is 15-20 minutes;
[0023] In this application, in view of the poor binding force and easy dissociation of the existing "base membrane + separation layer" composite membrane materials, the structure is regulated from the two aspects of the base membrane surface properties and the separation layer materials. From the perspective of the base membrane, firstly, the PEBAX polymer is used to modify the base membrane surface. Since the PEBAX material contains both ether bonds and amide bond structures, in which the ether bond is a flexible structure, the PEBAX material has good flexibility and can be stably bonded to the surface of the hollow fiber base membrane; secondly, the amide bonds rich in PEBAX can interact with the separation layer, which is also a polyamide material, to form hydrogen bonds, thereby improving the binding force between the base membrane and the separation layer. From the perspective of the separation layer, polyamines such as PEA, which are also rich in ether bonds, are used as polymerization monomers, and a polyamide separation layer with good flexibility can be obtained by reacting with polyacyl chlorides through an interfacial polymerization method. Therefore, the hollow fiber nanofiltration membrane material prepared according to the method described in this application is rich in ether bond flexible structures, and there is a hydrogen bond interaction between the separation layer and the base membrane surface. The above two factors make the hollow fiber nanofiltration membrane have excellent stability and can operate for a long time under a high-pressure and high-flow hydraulic environment.
[0024] Beneficial effects: Compared with the existing invention patents for modifying the surface of the base membrane (such as CN202010135374.X, CN202010690672.5, CN202110853756.0), the difference of this application is that a polymer with both ether bonds and amide bonds is used as the base membrane surface modification material, which not only increases the flexibility of the nanofiltration membrane material, but also strengthens the binding force between the separation layer and the base membrane surface, and significantly improves the structural stability of the polyamide nanofiltration separation layer on the curved surface of the hollow fiber. In addition, the present application also uses a polyetheramine monomer with an ether bond structure to increase the structural flexibility of the polyamide separation layer itself. In short, the present application introduces ether bond flexibility from both the base membrane modification and the separation layer material structure, and specifically solves the problem of long-term stability of the hollow fiber nanofiltration membrane. DETAILED DESCRIPTION
[0025] In order to evaluate the effectiveness of the method, the present application also prepared three different hollow fiber nanofiltration membranes as comparative examples, and the specific preparation process is shown below.
[0026] The test method for the flux and salt rejection rate of the hollow fiber nanofiltration membrane of the present invention is as follows:
[0027] Membrane separation performance test: The prepared hollow fiber nanofiltration membrane was pre-pressed with an electrolyte solution with a 0.2% mass concentration of MgSO4 at 0.4 MPa for half an hour to test the desalination performance and water flux of the hollow fiber nanofiltration membrane.
[0028] The calculation formula of water flux is shown in (1):
[0029]
[0030] Where A is the effective membrane area, m 2 ; t - the time required to collect Q volume of produced liquid, h; Q - the volume of produced liquid collected within t time, L.
[0031] The calculation method of membrane desalination performance is shown in (2):
[0032] (2)
[0034] Among them, R is the desalination rate, C f - Conductivity of the stock solution, μS / cm; C p - Conductivity of produced water, μS / cm.
[0035] Bonding strength test: In order to test the bonding strength between the separation layer and the base membrane, the above tested membrane was immersed in an ethanol solution for 24 hours. After washing, the separation performance was tested in the same way. The principle of the ethanol immersion method is that due to the difference in swelling coefficients of various materials, the base membrane and the separation layer will swell to varying degrees after being treated with ethanol solvent, resulting in a weakening of the stability at the interface. Therefore, this method can be used to test the size of the interfacial bonding strength. The test results are shown in Table 2.
[0036] Embodiment 1:
[0037] (1) A polysulfone hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 50,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0038] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in an isopropanol solution containing 0.2% (mass concentration) PEBAX for 2 minutes, wherein the molecular weight of PEBAX is selected to be 10000Da;
[0039] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 1 minute, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 40°C for 6 minutes;
[0040] (4) The outer surface of the basement membrane was re-immersed in a 2% (mass concentration) aqueous solution of PEA for 2 minutes, wherein the molecular weight of PEA was selected to be 200 Da; then, the basement membrane was taken out and hung vertically in the air for 1 minute, and the excess solution was wiped off with a paper towel;
[0041] (5) The base membrane is immersed in a 0.2% (mass concentration) pentane solution of trimesoyl chloride again and kept for 2 minutes. The base membrane is taken out from the solution and placed in a forced air drying oven at 80° C. for 15 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane is obtained.
[0042] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 93.4%; the water flux was 30.4L / m 2 .h; The hollow fiber nanofiltration membrane was soaked in ethanol solution for 1 hour and then taken out. The measured desalination rate was 93.1% and the water flux was 31.9 L / m 2 .h.
[0043] Embodiment 2:
[0044] (1) A polyethersulfone hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 40,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0045] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in a n-pentanol solution containing 0.3% (mass concentration) PEBAX for 3 minutes, wherein the molecular weight of PEBAX is selected to be 8000Da;
[0046] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 5 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 45°C for 7 minutes;
[0047] (4) re-immersing the outer surface of the basement membrane in a 3% (mass concentration) aqueous solution of PEA for 3 minutes, wherein the molecular weight of PEA is selected to be 400 Da; then taking it out and hanging it vertically in the air for 5 minutes, and wiping off the excess solution with a paper towel;
[0048] (5) The base membrane is immersed in a 0.3% (mass concentration) hexane solution of succinyl chloride again and kept for 5 minutes. The base membrane is taken out from the solution and placed in a 90°C forced air drying oven for 20 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane is obtained.
[0049] Performance test: The desalination rate of the hollow fiber nanofiltration membrane is 94.1%; the water flux is 33.2L / m 2 .h; The hollow fiber nanofiltration membrane was soaked in ethanol solution for 1 hour and then taken out. The measured desalination rate was 94.2% and the water flux was 34.6L / m 2 .h.
[0050] Embodiment 3:
[0051] (1) A polyethylene hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 80,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0052] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in a n-pentanol solution containing 0.4% (mass concentration) PEBAX for 4 minutes, wherein the molecular weight of PEBAX is selected to be 30000Da;
[0053] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 10 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 50° C. for 8 minutes;
[0054] (4) The outer surface of the basement membrane was re-immersed in a 4% (mass concentration) aqueous solution of PEA for 4 minutes, wherein the molecular weight of PEA was selected to be 2000 Da; then, the basement membrane was taken out and hung vertically in the air for 10 minutes, and the excess solution was wiped off with a paper towel;
[0055] (5) The base membrane was immersed in a 0.5% (mass concentration) cyclohexane solution of diphenyl diacetyl chloride again and kept for 5 minutes. The base membrane was taken out from the solution and placed in a 100° C. forced air drying oven for 20 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane was obtained.
[0056] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 93.7%; the water flux was 35.9L / m 2 .h; The hollow fiber nanofiltration membrane was soaked in ethanol solution for 1 hour and then taken out. The measured desalination rate was 92.9% and the water flux was 36.8L / m 2 .h.
[0057] Embodiment 4:
[0058] (1) A polypropylene hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 60,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0059] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in a n-hexanol solution containing 0.5% (mass concentration) PEBAX for 3 minutes, wherein the molecular weight of PEBAX is selected to be 10000Da;
[0060] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 8 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 50° C. for 8 minutes;
[0061] (4) re-immersing the outer surface of the basement membrane in a 4% (mass concentration) aqueous solution of PEA for 5 minutes, wherein the molecular weight of PEA is selected to be 400 Da; then taking it out and hanging it vertically in the air for 10 minutes, and wiping off the excess solution with a paper towel;
[0062] (5) The base membrane was immersed in a 1.5% (mass concentration) heptane solution of 4,4'-oxybis(benzoyl chloride) for 10 minutes, and the base membrane was taken out from the solution and placed in a 120°C forced air drying oven for 30 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane was obtained.
[0063] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 94.1%; the water flux was 28.8L / m 2 .h; The hollow fiber nanofiltration membrane was soaked in ethanol solution for 1 hour and then taken out. The measured desalination rate was 93.8% and the water flux was 30.5L / m 2 .h.
[0064] Embodiment 5:
[0065] (1) Using a polyvinylidene fluoride hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 70000Da) as a base membrane, immersing the hollow fiber ultrafiltration membrane in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, then immersing it in pure water for cleaning and standing for 6 hours for standby use;
[0066] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in an isopropanol solution containing 0.1% (mass concentration) PEBAX for 2 minutes, wherein the molecular weight of PEBAX is selected to be 8000Da;
[0067] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 5 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 45°C for 6 minutes;
[0068] (4) The outer surface of the basement membrane was re-immersed in a 1% (mass concentration) aqueous solution of PEA for 2 minutes, wherein the molecular weight of PEA was selected to be 400 Da; then, the basement membrane was taken out and hung vertically in the air for 1 minute, and the excess solution was wiped off with a paper towel;
[0069] (5) The base membrane is immersed in a pentane solution of trimesoyl chloride (0.2% by mass concentration) again for 2 minutes, and the base membrane is taken out from the solution and placed in a forced air drying oven at 80° C. for 15 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane is obtained.
[0070] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 94.7%; the water flux was 35.8L / m 2 .h; The hollow fiber nanofiltration membrane was immersed in the ethanol solution for 1 hour and then taken out. The measured desalination rate was 93.9% and the water flux was 37.3L / m 2 .h.
[0071] Embodiment 6:
[0072] (1) A polysulfone hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 80,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0073] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in an isopropanol solution containing 0.5% (mass concentration) PEBAX for 5 minutes, wherein the molecular weight of PEBAX is selected to be 10000Da;
[0074] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 6 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 40°C for 10 minutes;
[0075] (4) The outer surface of the basement membrane was re-immersed in a 4% (mass concentration) aqueous solution of PEA for 5 minutes, wherein the molecular weight of PEA was selected to be 2000 Da; then, the basement membrane was taken out and hung vertically in the air for 7 minutes, and the excess solution was wiped off with a paper towel;
[0076] (5) The base membrane was immersed in a 1% (mass concentration) cyclohexane solution of 4,4'-oxybis(benzoyl chloride) for 10 minutes, and the base membrane was taken out from the solution and placed in a 70°C forced air drying oven for 30 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane was obtained.
[0077] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 94.3%; the water flux was 30.7L / m 2 .h; The hollow fiber nanofiltration membrane was soaked in ethanol solution for 1 hour and then taken out. The measured desalination rate was 93.6% and the water flux was 35.2L / m 2 .h.
[0078] Embodiment 7:
[0079] (1) Using a polyvinylidene fluoride hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 60000Da) as a base membrane, immersing the hollow fiber ultrafiltration membrane in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, then immersing it in pure water for cleaning and standing for 6 hours for standby use;
[0080] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in a n-hexanol solution containing 0.2% (mass concentration) PEBAX for 3 minutes, wherein the molecular weight of PEBAX is selected to be 8000Da;
[0081] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 8 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 55° C. for 7 minutes;
[0082] (4) The outer surface of the basement membrane was re-immersed in a 4% (mass concentration) aqueous solution of PEA for 3 minutes, wherein the molecular weight of PEA was selected to be 200 Da; then, the basement membrane was taken out and hung vertically in the air for 9 minutes, and the excess solution was wiped off with a paper towel;
[0083] (5) The base membrane is immersed in a 0.3% (mass concentration) hexane solution of trimesoyl chloride again and kept for 6 minutes. The base membrane is taken out from the solution and placed in a 90°C forced air drying oven for 20 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane is obtained.
[0084] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 92.4%; the water flux was 33.7L / m 2 .h; The hollow fiber nanofiltration membrane was soaked in ethanol solution for 1 hour and then taken out. The measured desalination rate was 92.1% and the water flux was 36.3L / m 2 .h.
[0085] In order to further investigate the strengthening effect of the method of the present application on the stability of the hollow fiber nanofiltration membrane, the following comparative examples are added:
[0086] Comparative Example 1:
[0087] (1) A polysulfone hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 60,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0088] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, wipe off the excess solution with a paper towel, and then immerse the outer surface of the membrane in pure n-hexanol solution for 3 minutes;
[0089] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 8 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 40°C for 20 minutes;
[0090] (4) re-immersing the outer surface of the basement membrane in a 0.5% (mass concentration) piperazine aqueous solution for 3 minutes, then taking it out and hanging it vertically in the air for 10 minutes, and wiping off the excess solution with a paper towel;
[0091] (5) The base membrane is immersed in a 0.3% (mass concentration) hexane solution of trimesoyl chloride again and kept for 6 minutes. The base membrane is taken out from the solution and placed in a 100° C. forced air drying oven for 20 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane is obtained.
[0092] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 98.6%; the water flux was 22.8L / m 2 .h; The hollow fiber nanofiltration membrane was immersed in the ethanol solution for 1 hour and then taken out. The desalination rate was measured to be 84.4% and the water flux was 45.4L / m 2 .h
[0093] Comparative Example 2:
[0094] (1) A polysulfone hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 60,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0095] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, wipe off the excess solution with a paper towel, and then immerse the outer surface of the membrane in pure n-hexanol solution for 3 minutes;
[0096] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 8 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 40°C for 20 minutes;
[0097] (4) The outer surface of the basement membrane was re-immersed in a 0.5% (mass concentration) aqueous solution of PEA for 3 minutes, wherein the molecular weight of PEA was selected to be 400 Da, and then taken out and hung vertically in the air for 10 minutes, and the excess solution was wiped off with a paper towel;
[0098] (5) The base membrane is immersed in a 0.3% (mass concentration) hexane solution of trimesoyl chloride again and kept for 6 minutes. The base membrane is taken out from the solution and placed in a 100° C. forced air drying oven for 20 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane is obtained.
[0099] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 94.7%; the water flux was 25.6L / m 2 .h; The hollow fiber nanofiltration membrane was soaked in ethanol solution for 1 hour and then taken out. The measured desalination rate was 90.5% and the water flux was 31.4L / m 2 .h.
[0100] Comparative Example 3:
[0101] (1) A polysulfone hollow fiber ultrafiltration membrane (molecular weight cutoff ≈ 60,000 Da) was used as a base membrane, and the hollow fiber ultrafiltration membrane was immersed in a cleaning solution (30% by mass isopropanol aqueous solution) for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and allowed to stand for 6 hours for standby use;
[0102] (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, and wipe off the excess solution with a paper towel, then immerse the outer surface of the membrane in a n-hexanol solution containing 0.3% (mass concentration) PEBAX for 5 minutes, wherein the molecular weight of PEBAX is selected to be 10000Da;
[0103] (3) The base film was taken out from the alcohol solution, hung vertically in the air for 8 minutes, and the excess solution was wiped off with a paper towel, and then placed in a hot drying oven at 40°C for 20 minutes;
[0104] (4) re-immersing the outer surface of the basement membrane in a 0.5% (mass concentration) piperazine aqueous solution for 3 minutes, then taking it out and hanging it vertically in the air for 10 minutes, and wiping off the excess solution with a paper towel;
[0105] (5) The base membrane is immersed in a 0.3% (mass concentration) hexane solution of trimesoyl chloride again and kept for 6 minutes. The base membrane is taken out from the solution and placed in a 100° C. forced air drying oven for 20 minutes. After washing with water, a polyamide hollow fiber nanofiltration composite membrane is obtained.
[0106] Performance test: The desalination rate of the hollow fiber nanofiltration membrane was 98.5%; the water flux was 18.6L / m 2 .h; The hollow fiber nanofiltration membrane was immersed in the ethanol solution for 1 hour and then taken out. The desalination rate was measured to be 90.5% and the water flux was 38.8L / m 2 .h.
[0107] Table 1 Preparation conditions of hollow fiber nanofiltration membrane material comparative group samples
[0108]
[0109] a: Only pure solvents are used for processing
[0110] b: Polyamine monomers used in conventional nanofiltration membranes
[0111] Table 2 Differences in performance and stability of the membranes of the examples and comparative examples
[0112]
[0113]
Claims
1. A method for preparing a hollow fiber nanofiltration composite membrane with a stable and flexible structure, characterized in that The steps include: (1) A hollow fiber ultrafiltration membrane is used as a base membrane, and the hollow fiber ultrafiltration membrane is immersed in a 30% by mass isopropanol aqueous solution for cleaning, and the immersion treatment is performed for 6 hours to clean the organic solvent remaining in the base membrane, and then immersed in pure water for cleaning and standing for 6 hours for standby use; wherein the material of the ultrafiltration membrane can be one of polysulfone, polyethersulfone, polyethylene, polypropylene, or polyvinylidene fluoride; the molecular weight cutoff of the base membrane is ≈40000-80000Da; (2) After taking out the ultrafiltration base membrane, hang it vertically for 10 minutes, wipe off the excess solution, and then immerse the outer surface of the membrane in an alcohol solution containing a polyether block polyamide with a mass concentration of 0.1-0.5% for 1-5 minutes, wherein the molecular weight of the polyether block polyamide is one of 8000, 10000, or 30000 Da, and the alcohol solvent is one of isopropanol, n-pentanol, or n-hexanol; (3) taking the base film out of the alcohol solution, hanging it vertically in the air for 1-10 minutes, wiping off the excess solution, and then placing it in a hot drying oven at 30-60° C. for 5-10 minutes; (4) re-immersing the outer surface of the base film into an aqueous solution of polyetheramine with a mass concentration of 1-4% for 1-5 minutes, wherein the molecular weight of the polyetheramine is selected from 200, 400, or 2000 Da; then taking it out and hanging it vertically in the air for 1-10 minutes, and wiping off the excess solution; (5) immersing the base film again in a polyacyl chloride monomer organic phase solution with a mass concentration of 0.1-1% for 1-10 minutes, wherein the polyacyl chloride monomer is one of succinyl chloride, diphenyl diacetyl chloride, 4,4'-oxybis(benzoyl chloride), trimesoyl chloride or a mixture thereof, and the organic solvent is one of pentane, hexane, cyclohexane, heptane or a mixture thereof; (6) The base membrane is taken out from the organic phase, placed in a forced air drying oven at 60-120° C. for 10-30 minutes, and washed with water to obtain a polyamide hollow fiber nanofiltration composite membrane.
2. A preparation method according to claim, characterized in that: In step (1), the molecular weight cut-off of the hollow fiber ultrafiltration base membrane is 50,000-60,000 Da.
3. A preparation method according to claim, characterized in that: In step (2), the mass concentration of the polyether block polyamide is 0.2-0.4% and the molecular weight is 10000Da; the immersion time of the base film in the alcohol solution is 2-4 minutes.
4. A preparation method according to claim, characterized in that: In step (3), the heat treatment temperature is 40-50° C. and the heat treatment time is 6-8 minutes.
5. A preparation method according to claim, characterized in that: In step (4), the mass concentration of the polyetheramine is 2%-3% and the molecular weight is 400Da; the immersion time of the membrane in the aqueous phase is 2-4 minutes.
6. A preparation method according to claim, characterized in that: In step (5), the concentration of the polyacyl chloride monomer is 0.2%-0.5%; and the immersion time of the base film in the organic phase is 2-5 minutes.
7. A preparation method according to claim, characterized in that: In step (6), the oven temperature is 80-100° C. and the heat treatment time is 15-20 minutes.
Citation Information
Patent Citations
Preparation method of high performance organic gas separation film
CN106256417A
Polyvinylidene fluoride composite nanofiltration membrane for sewage treatment and preparation method thereof
CN108079802A
Sulfonated Cardo polyethersulfone polymer containing amido, synthesis method of sulfonated Cardo polyethersulfone polymer, and reverse osmosis composite membrane
CN110527093A
Pebax carbon membrane, preparation method thereof and application of Pebax carbon membrane in H2 / CO2 separation
CN116585901A
A preparation of asymmetric porous peba membrane for composite membrane
KR1020090033733A